ANALYSIS OF PROCESSING PALM OIL FRUIT INTO CRUDE PALM OIL AT PT. SEDJAHTERA INDO AGRO BUKIT AJONG FACTORY, SANGGAU DISTRICT - Ma'sum, Zuhdi; Lorenza, Karolina Maret; Ratna, Kornelia (Teknik Kimia ITN Malang, 2023)
An analysis of the production process needs to be done at PT. Sedjahtera Indo Agro PKS Bukit Ajong Factory. The method was determining the average, median, standard deviation, and variance free fatty acid content of production. Free fatty acid levels was titrated by 0.1N NaOH and Phenolphthalein as an indicator. The results of the analysis of 461 samples found that the average percent free fatty acid content was 3.76% with a median of 3.95. The variance value is 0.05 with a standard deviation of 0.17. The factors causing unstable levels of free fatty acids is due to non-continuous factory operations and frequent stoppages of operations. If that happens for a long time, the free fatty acid levels will increase as a result of the increase in temperature in the tank. However, the CPO produced still meets the SNI where the average FFA content per week is 2-5%.